EVALUASI UNJUK KERJA KOMUNIKASI DATA PAKET PADA SISTEM KOMUNIKASI SELULAR (KASUS CELLULAR DIGITAL PACKET DATA) - Pudji Astuti (NIM : 23295007), Rina
Abstract : A Cellular Communication System is not only fit to be used as a voice communication but also as data communication system. Two solutions are offered to use Cellular Communication System as a data communication system, i.e. standalone system which entire bandwidth is used to transmit data and overlay system which data are transmitted overlay above cellular communication system. This research is focused on the second solution, especially a data communication system application, CDPD system, overlaid above an analog cellular communication system, AMPS. Theoretical analysis was used to verify the performances of the data communication system. The analysis included an effect of the data communication on voice communication users, throughput, average delay and normalised voice traffic loss. Two categories of channel assignment algorithms are used on the CDPD system, i.e. a dedicated channel algorithm and frequency hop-ping algorithm. The analysis that has been conducted, verified that the application of the dedicated channel algorithm will reduce the number of voice channels, so the blocking probability of voice traffic, Pbio,k, will increase. The use of omni-directional antenna gives a better voice traffic quality than a sector antenna using. On the other hand, the application of frequency hopping algorithm will increase cellular system channels utilisation, due to an unused voice channel can be employed to carry data traffic, but at a cost of a decrease in the carrier to interference ratio Cll. The use of sector antenna will give a CDPD system better performance than an omni-directional antenna, but will increase normalised voice traffic loss.